(untitled) (Journal of Dhaka Medical College, 2021)
Background : Chronic renal disease changes both quality and quantity of bone through multifactorial influences on bone metabolism, leading to osteopenia, osteoporosis and increased risk of fracture. The objectives of this cross sectional study are to determine the mean bone mineral density (BMD) and to identify osteopenia and osteoporosis in patients of CKD on maintenance hemodialysis. Methods: Twenty three male and 18 female patients with age between 18 and 50 years were enrolled in this study. The BMD of the lumbar vertebral spine (LV) and the neck of femur (FN) were measured in all patients. Data were analyzed using SPSS version 20.0 software and the level of significance was considered as P <0.05. Results: The mean BMD in the LV (L2-L4) was 1.18 ± 0.19 gm/cm2 in male and 1.04 ± 0.13 gm/cm2 in female patients (P =0.011). The mean BMD in the FN was 0.90 ± 0.19 gm/cm2 in male and 0.77 ± 0.15 g/cm2 in female patients (P = 0.022). Based on the World Health Organization criteria, 26.0% of the male and 22.2% of the female patients in our study had normal BMD; 39.2% male and 38.9%female patients had osteopenia, while 34.8% male and 38.9% female patients had osteoporosis .This study showed a marked decrease in mean BMD in the cortical bone (FN) compared with trabecular bone (LV) (P = 0.001) as well as in female patients on maintenance hemodialysis compared with male patients . Significant negative correlation (r= -0.480; p=0.001) was found between duration of hemodialysis and bone mineral density (BMD) in lumbar spine and femoral neck. Conclusion: The measurement of BMD is a good non-invasive screening test for renal bone disease and that a high number of patients with CKD stage 5 on maintenance hemodialysis have markedly decreased BMD. J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 3-11